2008
DOI: 10.1021/op8002129
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Assessment, Testing Decisions, and Analytical Determination of Genotoxic Impurities in Drug Substances

Abstract: The assessment and control of genotoxic impurities (GTI) in pharmaceutical products has received considerable attention in recent years. Molecular functional groups that render starting materials and synthetic intermediates useful as reactive building blocks for small molecules may also be responsible for their genotoxicity. As a potential safety concern, it is important to understand the various issues related to GTIs and how they can be addressed for clinical and commercial phases of development. Justificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 22 publications
0
60
0
Order By: Relevance
“…This is because these impurities are typically the most difficult to purge and as a consequence may need to be added to the final API specification (i.e., option 1 in the ICH M7 guidance 4 ). Four stages back from the API was chosen to reflect commentary by Pierson et al, 16 who indicated that a reactive intermediate can typically be purged effectively if it is introduced four or more stages prior to the final API isolation stage (i.e., option 3 in the ICH M7 guidance 4 ). This is obviously a coarse measure, as it takes no account of the prevailing downstream chemistry or the total number of synthetic stages in the process (and indeed, some of the syntheses reported here have ≤4 stages in total).…”
Section: ■ Discussionmentioning
confidence: 99%
“…This is because these impurities are typically the most difficult to purge and as a consequence may need to be added to the final API specification (i.e., option 1 in the ICH M7 guidance 4 ). Four stages back from the API was chosen to reflect commentary by Pierson et al, 16 who indicated that a reactive intermediate can typically be purged effectively if it is introduced four or more stages prior to the final API isolation stage (i.e., option 3 in the ICH M7 guidance 4 ). This is obviously a coarse measure, as it takes no account of the prevailing downstream chemistry or the total number of synthetic stages in the process (and indeed, some of the syntheses reported here have ≤4 stages in total).…”
Section: ■ Discussionmentioning
confidence: 99%
“…have the ability to remove GTIs along with other process impurities. Purging of impurities was previously addressed by Pierson et al 27 The risk of GTI carry over was defined considering the number of synthetic steps between the point of GTI appearance and final production step. If the GTI appears more than four steps before the final step, chemical rationale could be used to assess the need of GTI removal.…”
Section: Key Pointsmentioning
confidence: 99%
“…The genotoxic impurity testing point can vary and needs to be determined with scientific basis and supporting data . The testing strategy for PGIs analysis is shown in Fig.…”
Section: Genotoxic Impurities Assessment and Controlmentioning
confidence: 99%